Supervised consumption sites and crime: scrutinizing the methodological weaknesses and aberrant results of a government report in Alberta, Canada - James D. Livingston (BMC, 2021)
Abstract To date, peer-reviewed research has found no evidence linking supervised consumptions sites (SCSs) to increased crime. Yet, in March 2020, a government Report released in the province of Alberta, Canada, presented the results of a review that reached a different conclusion. This commentary highlights the Report's major methodological limitations with respect to its criminological components, including that crime was poorly operationalized and measured, change in crime was inadequately assessed, and the effect of SCSs on crime was not ascertained. It is argued that the magnitude of methodological flaws in the Report undermine the validity of its criminological claims and raise significant issues with the soundness of its conclusions.